A woman saint in the Parisian colleges: Claude Roillet's Catharinae Tragoedia (1556). Issue 4 (September 2016) - Nassichuk, John
Abstract: This article introduces and examines a hitherto little‐discussed tragedy by the French humanist Claude Roillet, professor and principal at the Collège de Bourgogne in the University of Paris during the reign of Henri II. This brief five‐act play entitled Catharinae tragedia, which presents the life of the iconic saint Catherine of Alexandria, based principally upon information gleaned from late‐mediaeval, Latin prose sources, was first printed amongst the author's collected Varia Poemata in 1556. This study shall examine Roillet's debt to his Latin sources, with some consideration of possible influences exercised by the vernacular, dramatic mysteries devoted to Catherine and presented in France during the first half of the sixteenth century. The objective is to situate this Latin play within the tradition of texts of all genres devoted to this well‐known character who is frequently met with in mediaeval and early Renaissance iconography. The article will also discuss the didactic aspects proper to Roillet's presentation of the story.